Looks and Labor: Do Attractive People Work More?. (September 2014) - Gehrsitz, Markus
Abstract Using the German General Social Survey (ALLBUS) 2008, I investigate how looks affect an individual's labor supply decision. My results are, by and large, in line with predictions derived from the neoclassical model of labor supply. Applying regular probit, bivariate probit, Tobit and Heckman selection regression models, I find that good looks go hand in hand with higher employment probabilities and more hours of market work. Furthermore, physical attractiveness is positively associated with spousal income and spousal employment. Hence, beauty appears to affect labor supply decisions both directly and through the marriage market.